Effect of transition metal ion substitution on thermostable T1 lipase activity - Harun, Harmiza (2013)
This study involved the effect of transition metal ion removal and substitution on lipase activity and thermostability. The role of metal ions in the activity and stability of the enzyme was studied using the holoenzyme, apoenzyme and metal substituted enzyme. T1 lipase from Geobacillus zalihae contains a structural zinc ion (Zn2+) that apparently contributes to the high temperature tolerance. This Zn2+ ion is tightly bound to histidine (H81 and H87) in the catalytic domain and aspartate (D61 and D238) in the extra domain of T1 lipase. Initially, Molecular Dynamics (MD) simulation using YASARA software was performed at 343 K and pH 9 to determine the changes in the protein structure, dynamics and flexibility of T1 lipase affected due to Zn2+ ion depletion. Interestingly, D238, H81 and H87 which also the Zn2+ ion binding ligand, were found to be highly fluctuated in the absence of Zn2+ ion which may have caused weaker intramolecular interaction of zinc ion-binding coordination. The stability of T1 lipase and apo-T1 lipase was estimated based on the Gibbs free energy (ΔG) analysis using FoldX software. Based on the ΔG value calculated, the stability of apo-T1 lipase was reduced to -53 kcal/mol as compared to T1 lipase, -65 kcal/mol. Hence, it is suggested that Zn2+ ion contributes to the stability of T1 lipase at elevated temperature. The role of the Zn2+ ion was elucidated by its elimination from the structure of T1 lipase with two metal chelators such as, 2,6- pyridinedicarboxylic acid (2,6-PDCA) and N,N,N’,N’-tetrakis-(2-pyridylmethyl) ethylenediamine (TPEN). Among them, the incubation of T1 lipase with TPEN removed almost up to 100 % of the Zn2+ ion followed by 83 % removal by 2,6-PDCA. The specific activity of apo-T1 lipase was decreased (84 U/mg) as compared to T1 lipase (104 U/mg), thus confirming the role of Zn2+ ion in the stability of T1 lipase. This data is supported by the details obtained in the thermostability study and half-life study of both lipases. T1 lipase has been modified by means of transition metal ion replacement in order to improve its enzymatic activity and protein stability at high temperature. Three potential transition metal ions such as Mn2+ ion, Pd2+ion, and ruthenium ion (Ru3+) has been added in apo-T1 lipase via dialysis at 4 oC. Zn2+ ion in T1 lipase was successfully replaced by Mn2+ ion and Pd2+ ion with the ratio of 1 mol of protein to ~1 mol of transition metal ion. The specific activity of Mn2+-T1 lipase and Pd2+-T1 lipase was enhanced about 1.6 fold and 1.1 fold respectively. However, the substitution of T1 lipase with Ru3+ was unsuccessful due to enzyme inactivation. The biochemical and biophysical characterization of T1 lipase and apo-T1 lipase was performed. Both lipases shared the same optimum temperature which is 70 oC. However, the removal of Zn2+ has reduced the thermostability and half live (t1/2) of T1 lipase by 10 oC and 20 minutes rescpectively. The fluorescence emission spectra showed the maximum intensity (λmax) was red-shifted from 433 nm to 511 nm due to the elimination of Zn2+ ion. This change ascribed the decrease of the exposure of hydrophobic cavity in apo-T1 lipase. In addition, the changes in the stability and activity of T1 lipase and apo-T1 lipase were investigated during denaturation by urea. An increased in the denaturant concentration has drastically induced inactivation and unfolding of both lipases. In the absence of Zn2+ ion, the maximal fluorescence emission spectrum of T1 lipase was red shifted to a maximum value of 355 nm. The effect of transition metal ion chelation and addition on the structure of T1 lipase was observed using Circular Dichroism (CD) based on the changes in the secondary structure components, such as, α-helix, β-sheet, turn and random coil. Fascinatingly, the addition of Mn2+ ion and Pd2+ ion into the apoenzyme increased the thermal denaturation (Tm) point based on the CD analysis. In conclusion, experimental analysis performed in this study highlighted the understanding of holding the catalytic and extra domains together with a metal ion can stabilize this lipase; changing the metal ion can increase this stability. This work sets the foundation for the design of T1 lipase as a metal ion biosensor.